Developing the infrastructure for managing institutional research archives - Tsolakidis, Anastasios; Triperina, Evangelia; Triantafyllou, Ioannis; Skourlas, Christos (Journal of Integrated Information Management, 2023)
Purpose - Capturing research in modern academic institutions is of vital importance. A robust approach to systematically harvest, host, and update a university-wide repository is not only beneficial for the academics within the HEI, but it can also boost and promote the visibility of the University. Design/methodology/approach - Although many decentralized approaches offer the possibility to showcase an individual’s research, the vast and disparate sources cannot facilitate an institutional repository. Since research constitutes one of the main aims of a university, we follow a solution that records the whole research that occurs within an institution, which is VIVO. In this paper, we present the adaptation of VIVO by a Greek University, namely, the University of West Attica. In our approach, we have merged the existing systems and harvested research-related information from different sources on the web. Findings - The proposed solution serves as an academic research repository. It provides consistency over the presented research outputs, making the research of the University wider visible. Originality/value - The paper presents an ontology-based system for documenting the undertaken research within an institution. Moreover, it allows the personalization of the ontology, thus making it possible to customize the repository to fit an institution’s needs, the web interface, therefore presenting the perceived significant components for the University, and the information visualization.